The Implementation of the Harmony of Citizens’ Rights and Obligations among English Language Education Students in the Era of Globalization - Cheria Nathasia Bernel Doko; Apolonia Laura Ndalo; Chofifah Khairunisa B Usman; Maria Eno Meo; Marista Ovradima Ga; Alfret Benu; Tans Feliks (Peneliti.net, 2026)
T In the era of globalization, university students have many opportunities to access information, education, and more comprehensive experiences through advances in technology and communication. The purpose of this study is to understand the implementation of harmony between the rights and obligations of citizens among students of the English Education Department, Faculty of Teacher Training and Education (FKIP). The method used in this study is a literature review by examining several references, such as books, journals, and relevant laws and regulations. Based on the results of the study, it can be understood that students have obtained several rights, such as the right to education and the right to access information. In addition, students also have several obligations, such as obeying regulations, respecting the rights of others, and participating in social life within the community.